2012
DOI: 10.3109/17482941.2012.682070
|View full text |Cite
|
Sign up to set email alerts
|

Transient apical ballooning accompanying respiratory infection

Abstract: We report the case of a 75-year-old man, referred for worsening dyspnea and fever. The electrocardiography (ECG) showed mild ST-elevation in anterior leads, while cardiac echography severe left ventricular (LV) systolic dysfunction with apical ballooning. Later on, ECG showed negative T-waves and QT-prolongation in the same anterior leads and T-waves positivization during fever peak. Ten days later, LV ejection fraction completely recovered, apical ballooning and fever disappeared. We, therefore, hypothesize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Of a total of 1725 articles found [1341 with the precise Medical Subject Headings term (TTC)], we selected 26 articles dealing with 27 case reports (Table 1), 12 37 with an expected higher prevalence of women (n = 20, 74.1%). The mean age was 61.4 ± 13.7 years and bacterial infections were more frequent (n = 23, 85.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Of a total of 1725 articles found [1341 with the precise Medical Subject Headings term (TTC)], we selected 26 articles dealing with 27 case reports (Table 1), 12 37 with an expected higher prevalence of women (n = 20, 74.1%). The mean age was 61.4 ± 13.7 years and bacterial infections were more frequent (n = 23, 85.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studied have linked several infections to TTC, including pulmonary infection and upper respiratory tract infection [9] , [10] . De Giorgi et al reviewed 27 reported case related to acute infection-induced TTC, found that it most frequently affects female and caused by bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, apical ballooning was caused by phenylephrine inhaled for relieving nasal congestion [9]. Stress cardiomyopathy, however, is not uncommon even in case of respiratory infection [10].…”
mentioning
confidence: 99%